Mortality reduction in 46 patients with severe COVID-19 treated with hyperimmune plasma. A proof-of-concept, single-arm, multicenter trial - Perotti, Cesare; Baldanti, Fausto; Bruno, Raffaele; Del Fante, Claudia; Seminari, Elena; Casari, Salvatore; Percivalle, Elena; Glingani, Claudia; Musella, Valeria; Belliato, Mirko; Garuti, Martina; Meloni, Federica; et al. (Haematologica (Roma), 2020)
Hyperimmune plasma from patients convalescing from COVID-19 is a potential treatment for severe COVID-19 in other patients. We conducted a multicenter, one-arm, proof-of-concept interventional study. Patients with COVID-19 with moderate-to-severe acute respiratory distress syndrome, elevated C-reactive protein level and need for mechanical ventilation and/or continuous positive airway pressure were enrolled. One to three units (each of 250-300 mL) of hyperimmune plasma (neutralizing antibody titer ≥1:160) were administered. The primary outcome measure was 7-day hospital mortality. Secondary study outcomes were PaO2/FiO2, changes in laboratory and radiological parameters, weaning from mechanical ventilation and safety of the intervention. The study enrolled 46 patients between March 25 and April 21, 2020. The mean age of the patients was 63 years and 61% were male. Thirty of the patients were on continuous positive airway pressure and seven were intubated. The mean PaO2/FiO2 was 128 (standard deviation [SD] 47). Bilateral infiltrates on chest X-ray were present in 36 patients (84%). The mean duration of symptoms and ARDS was 14 (SD 7) and 6 (SD 3) days, respectively. Three patients (6.5%) died within 7 days as compared to an expected 15% according to national statistics and 30% in a small concurrent cohort of 23 patients. The upper one-sided 90% confidence interval (CI) was 13.9%, allowing rejection of the null hypothesis of a 15% mortality. The PaO2/FiO2 increased by 112 units (95% CI: 82-142) in survivors and the severity of the chest X-ray findings decreased in 23% (95% CI: 5%-42%). C-reactive protein, ferritin and lactate dehydrogenase levels decreased by 60%, 36% and 20%, respectively. Weaning from continuous positive airway pressure was achieved in 26/30 patients and it was possible to extubate three of the seven patients who had been intubated. Five serious adverse events occurred in four patients (2 likely and 2 possibly treatment-related). In conclusion, hyperimmune plasma showed promising benefits in COVID-19. Although these benefits need to be confirmed in a randomized controlled trial, this proof-of-concept study could open the way to future developments including hyperimmune plasma banking, standardized pharmaceutical products and monoclonal antibodies.